2022
DOI: 10.1371/journal.pone.0270969
|View full text |Cite
|
Sign up to set email alerts
|

Multi-attribute temporal descriptive methods in sensory analysis applied in food science: Protocol for a scoping review

Abstract: Background Sensory perception is a temporal phenomenon highly present in food evaluation. Over the last decades, several sensory analysis methods have been developed to determine how our processing of the stimuli changes during tasting. These methods differ in several parameters: how attributes are characterized (intensity, dominance or applicability), the number of attributes evaluated, the moment of sample characterization (simultaneously with the tasting in continuous or discrete time, retrospectively), the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(13 citation statements)
references
References 44 publications
0
13
0
Order By: Relevance
“…This scoping review was conducted according to the PRISMA Extension for Scoping Reviews (PRISMA‐ScR, Tricco et al., 2018). It was registered, reviewed, and published in PLoS ONE (Visalli & Galmarini, 2022). Hereafter is a summary of the original reviewed and published protocol (Figure 1).…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations
“…This scoping review was conducted according to the PRISMA Extension for Scoping Reviews (PRISMA‐ScR, Tricco et al., 2018). It was registered, reviewed, and published in PLoS ONE (Visalli & Galmarini, 2022). Hereafter is a summary of the original reviewed and published protocol (Figure 1).…”
Section: Methodsmentioning
confidence: 99%
“…The main criteria for inclusion were research articles, available in Web of Science and/or Scopus, referencing multi‐attribute temporal descriptive sensory evaluation methods, related to the evaluation of food and beverages (nonfoods were considered out of scope) or to methodological/data analysis issues. Further details and research equations can be found in Visalli and Galmarini (2022).…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…31 This method provides a more comprehensive insight compared to traditional static sensory evaluations, capturing the entire sensory experience from the initial perception to the aftertaste. 32 From the TI sensory evaluation experiment, the umami perception intensity for each umami peptide and the 0.3% MSG solution was obtained every second within 100 s. By averaging the sensory data from the 10 panelists, the TI curves for each umami peptide and the 0.3% MSG solution were derived, as shown in Figure 4.…”
Section: Sensory Evaluationmentioning
confidence: 99%